(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Chronic kidney diseases are growing problems among the population in both developing and developed countries. The number of individuals in the world who are at risk of end-stage renal disease is increasing. Among the key reasons for the increasing incidence of chronic kidney diseases is the lack of understanding of the routes of fundamental kidney disease and the deficient delivery of evidence-based treatment. This study presents records, trends and projections of aetiology-based chronic kidney disease incidence in Maiduguri, Nigeria. A desktop review was conducted using keywords such as "kidney disease" and "kidney disease in Maiduguri," individually and in combination. In addition, the records and trends of kidney disease in Maiduguri were studied using records available in the University of Maiduguri Teaching Hospital. The study revealed that there is a wide range of publications on the keywords worldwide, which were 18280 and 1790 publications (journal articles, books, conference proceedings) available through several search engines globally and Maiduguri, respectively. The record established that period (F9, 27 = 2.53; p = 0.03) and gender (F3, 27 = 2.54; p = 0.08) were significant factors that influenced the increasing trend of Maiduguri at a 95 % and 90 % confidence levels, respectively. It was concluded that there is an increase in cases of chronic kidney disease (ChKD) in Maiduguri, and there is a correlation between the number of kidney patients and the population